Effectiveness Test of Avocado Seed Extract (Persea Americana Mill.) in Inhibiting the Growth of Staphylococcus aureus Bacteria In Vitro - Indra Basar Siregar; Isnandar; Rahmi Syaflida Dalimunte; Melenia, Prilisa (Eureka Herba Indonesia, 2023)
Staphylococcus aureus can cause several health problems in the oral cavity, including stomatitis, tooth abscess, soft tissue infections, gingivitis, and periodontitis. The exploration of new therapeutic modalities for Staphylococcus aureus infection is urgent. Staphylococcus aureus has developed resistance to many of the antibiotics commonly used to treat bacterial infections. This study aimed to determine the antibacterial effectiveness of avocado seed extract (Persea americana Mill.) in inhibiting bacterial growth of Staphylococcus aureus in vitro. This study is an in vitro study in which 28 petri dishes have been added with 1-2 oses of bacterial culture Staphylococcus aureus and MHA (Mueller Hinton Agar) were used in this study. There were 7 test groups, namely 0.2% chlorhexidine as a positive control (K1), negative control, DMSO (K2), avocado seed extract treatment group 2%, 4%, 6%, 8%, and 10% respectively as K3-K7. Treatment of avocado seed extract with a concentration of 6% has the ability to grow bacteria Staphylococcus aureus better than the bacterial growth ability of the positive control, chlorhexidine. The increase in extract concentration was in line with the increase in the diameter of the bacterial inhibition zone Staphylococcus aureus. Avocado seed extract (Persea americana mill.) showed effectiveness in inhibiting bacterial growth of Staphylococcus aureus in vitro.